A novel approach to assessing the ecosystem‐wide impacts of reintroductions. Issue 1 (20th November 2018) - Baker, Christopher M.; Bode, Michael; Dexter, Nick; Lindenmayer, David B.; Foster, Claire; MacGregor, Christopher; Plein, Michaela; McDonald‐Madden, Eve
Abstract: Reintroducing a species to an ecosystem can have significant impacts on the recipient ecological community. Although reintroductions can have striking and positive outcomes, they also carry risks; many well‐intentioned conservation actions have had surprising and unsatisfactory outcomes. A range of network‐based mathematical methods has been developed to make quantitative predictions of how communities will respond to management interventions. These methods are based on the limited knowledge of which species interact with each other and in what way. However, expert knowledge isn't perfect and can only take models so far. Fortunately, other types of data, such as abundance time series, is often available, but, to date, no quantitative method exists to integrate these various data types into these models, allowing more precise ecosystem‐wide predictions. In this paper, we develop mathematical methods that combine time‐series data of multiple species with knowledge of species interactions and we apply it to proposed reintroductions at Booderee National Park in Australia. There have been large fluctuations in species abundances at Booderee National Park in recent history, following intense feral fox ( Vulpes vulpes ) control, including the local extinction of the greater glider ( Petauroides volans ). These fluctuations can provide information about the system isn't readily obtained from a stable system, and we use them to inform models that we then use to predict potential outcomes of eastern quoll ( Dasyurus viverrinus ) and long‐nosed potoroo ( Potorous tridactylus ) reintroductions. One of the key species of conservation concern in the park is the Eastern Bristlebird ( Dasyornis brachypterus ), and we find that long‐nosed potoroo introduction would have very little impact on the Eastern Bristlebird population, while the eastern quoll introduction increased the likelihood of Eastern Bristlebird decline, although that depends on the strength and form of any possible interaction.